2002
DOI: 10.1177/107110070202300209
|View full text |Cite
|
Sign up to set email alerts
|

Single Stage Correction with External Fixation of the Ulcerated Foot in Individuals with Charcot Neuroarthropathy

Abstract: The ulcerated foot in individuals with Charcot neuroarthropathy presents a complex problem when correction of the deformity is necessary but the presence of infection precludes the use of internal fixation. We reviewed 11 patients with midfoot Charcot neuroarthropathy, collapse, and ulceration who were at risk for amputation. These patients underwent operative debridement, corrective osteotomy, external skeletal fixation and culture-directed antibiotic therapy as a limb salvage procedure. Patients were transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 13 publications
0
70
0
1
Order By: Relevance
“…Although complications will be discussed in a separate section, the reader should be cautioned that, in the author's experience, complication rates (especially pin track irritation and infection) occur at a higher rate than those reported above and should be handled accordingly. 9 In 2002, Farber et al 10 reported 11 patients with midfoot Charcot arthropathy and ulceration. A single-stage procedure was performed consisting of debridement, corrective osteotomy and application of a Hoffman-type external fixator.…”
Section: Recent Literaturementioning
confidence: 98%
“…Although complications will be discussed in a separate section, the reader should be cautioned that, in the author's experience, complication rates (especially pin track irritation and infection) occur at a higher rate than those reported above and should be handled accordingly. 9 In 2002, Farber et al 10 reported 11 patients with midfoot Charcot arthropathy and ulceration. A single-stage procedure was performed consisting of debridement, corrective osteotomy and application of a Hoffman-type external fixator.…”
Section: Recent Literaturementioning
confidence: 98%
“…In these cases, Charcot reconstruction is necessary for limb salvage. Charcot reconstruction has been shown to be an effective method of correcting the deformity and providing a stable, plantigrade, foot [30][31][32][33].…”
Section: Plantar Pressure Magnitude In Cn Patientsmentioning
confidence: 99%
“…External fixation as an alternative to internal fixation allows rapid mobilization and is the subject of several papers [11,12]. Although some claim no pin tract infections, this seems unlikely since even non-diabetic patients regularly have infections if the system is used over an extended period of time.…”
Section: Arthrodesismentioning
confidence: 99%
“…plates, screws [10] and intramedullary nails [11,12] are used). The resection of metatarsal heads or bony prominences has also been described [13] and partial or total calcaneal resection is reported [14].…”
Section: S35mentioning
confidence: 99%